Comparing self‐reported and clinically diagnosed unmet dental treatment needs using a nationally representative survey. (13th February 2017) - Farmer, J.; Ramraj, C.; Azarpazhooh, A.; Dempster, L.; Ravaghi, V.; Quiñonez, C.
Abstract: Objectives: To describe the validity and diagnostic accuracy of self‐reported data compared with clinically assessed data for the ascertainment of clinical dental treatment needs in the Canadian population. Methods: A secondary analysis of data from the Canadian Health Measures Survey (2007‐2009) was undertaken. Clinical treatment needs were classified into preventive and diagnostic, restorative, endodontic, periodontic, surgical, and orthodontic categories. Sensitivity, specificity, positive and negative predictive values (NPVs), kappa statistics and likelihood ratios (LR) were calculated to compare self‐reported and clinically determined needs. Survey weights were applied to generate nationally representative findings of the Canadian population. Results: Generally across most dental need categories, agreement between self‐reported and clinically‐determined dental need was found to be moderate to poor (kappa <0.6). For most needs, self‐reported data was found to be highly specific (>90 percent) but not very sensitive. Low positive (<60 percent) and high NPVs (>80 percent) revealed that self‐reported information was found to be more precise in reassuring when most dental needs were not present, opposed to confirming needs that were required. High positive LRs were obtained for endodontic (+LR = 12.15) and orthodontic needs (+LR = 14.82), indicating good diagnostic accuracy of positive self‐report for these outcomes. Conclusions: Our findings suggest that in general, self‐reports are poor estimates for normative dental treatment needs but do have some merit in confirming non‐needs. Exceptionally, self‐reports do have suitable diagnostic accuracy for predicting orthodontic and endodontic needs.